PULMONARY MANIFESTATIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS VISITING TERTIARY CARE HOSPITAL - Dahani, Assadullah; Nasrullah Aamer; Nand Lal Seerani; Muhammad Tariq Karim; Furqan Khan; Shafique Rehman Arain. (Journal of Ayub Medical College Abbottabad, 2022)
Background: Rheumatoid arthritis is a common problem in elderly individuals. It is reported that lung involvement in these patients is widely present. This study was done with the purpose to assess the burden and characteristics of lung involvement in rheumatoid arthritis patients attending rheumatology clinic. Methods: This descriptive cross-sectional study, in which data was retrospectively collected, was carried out from April 2019 to December 2020 at the Rheumatology Department of Jinnah Postgraduate Medical Centre (JPMC), Karachi, Pakistan. All adult rheumatoid arthritis individuals, irrespective of gender or duration of disease, were consecutively enrolled. Information regarding the baseline characteristics, medication history for rheumatoid arthritis, findings of immunological tests along with the frequency of lung involvement and its pattern were observed. Results: Of 254 patients, the mean age was 37.46 ±12.39 years. Females were predominantly higher as compared to males, i.e., 232 (91.3%) vs. 22 (8.7%) respectively. Current smoking status was found positive in 7 (2.8%) patients. The mean disease duration was 4.41 ±3.96 years. Furthermore, frequency of pulmonary manifestation was observed in 45 (17.7%) patients. A significantly higher mean difference of age (p-value <0.001) and disease duration (p-value <0.001) was observed among patients with and without pulmonary manifestation. Moreover, a significant association of current smoker was also observed with pulmonary manifestation. Conclusion: A considerable number of patients with rheumatoid arthritis had pulmonary manifestation. Furthermore, a significant relationship was observed with age, duration of disease, and current smokers.